Pengaruh Penambahan Ekstrak Kulit Buah Naga (Hylocereus polyrhizus) terhadap Karakteristik Krim Kunyit dan Daun Asam - Pagur, Yohanes Wiliam; Mulyani, Sri; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 4 (2020): DesemberDO - 10.24843/JRMA.2020.v08.i04.p10, 2020)
The purpose of this study was to determine the effect of dragon fruit peel extract (Hylocereus polyrhizus) on the characteristics of turmeric cream and tamarind leaves. The concentration of dragon fruit peel extract treatment consisted of 6 levels, namely 0, 5, 10, 15, 20 and 25%. Each treatment was repeated 3 times, so that 18 experimental units were obtained. The variables observed in turmeric cream and tamarind leaves were homogeneity, viscosity, pH, dispersibility, adhesion, and separation ratio, antioxidant capacity, LAB color test. Data were observed and analyzed using a completely randomized design. The results showed that the extract of dragon fruit peel did not affect homogeneous separation ratio, viscosity, spread power, pH and antioxidant capacity, while color testing affected the brightness level of the cream and the yellowish value b. All treatments adding water extract of dragon fruit peel produce turmeric cream and tamarind leaves that are homogeneous, there is no separation, viscosity 6766-6850cP, spread ability 5.9-6.27 cm, adhesion 54.67-72.33s, pH 5.37-5.57, nalia color test values L 38.72 – 46.08, values A 27.41-34.98 values B 31.56-44.65 and antioxidant capacity 91,67-112,17. Keywords: Dragon fruit, turmeric and tamarind leaves, cream characteristics.